A STUDY OF SERUM MAGNESIUM AND CALCIUM LEVELS IN MISSED ABORTION (Iraqi Journal of Medical Sciences, 2016)
Background:Pregnancy is considered as a physiological stress, normal static metabolism of a woman is changed into dynamic anabolism, calcium (Ca) is the first most abundant cation in the human body, whereas magnesium (Mg) is the fourth most abundant one, role of calcium and magnesium in enzymatic activity of cell to release energy is well established.Objective:To assess the relation of serum magnesium and calcium levels in cases of missed abortion.Methods:Eighty two pregnant women at their 1st and 2nd trimester of pregnancy (before 24 completed weeks of pregnancy), 42 of them with missed abortion compared with 40 normal pregnancies served as a control group. Calcium analysis done using manual colorimetric method while magnesium analysis was done by magnesium calmogite method at the hospital laboratories.Results:Serum calcium was found to be insignificantly altered while serum magnesium was found to be significantly reduced in cases of missed abortion compared with normal pregnancy. Serum Ca/Mg ratio was found to be significantly elevated in cases of missed abortion compared with normal controls.Conclusion:Estimation of serum magnesium and Ca/Mg ratio in selected pregnancies can be valuable parameters for predicting missed abortion.Keywords:Missed abortion, Serum Calcium, Serum Magnesium.
Keywords: Missed abortion; Serum Calcium; Serum Magnesium